Hypertension management dynamics in pediatric CKD: Insights From the 4C Study - Doyon, Anke; Bayazit, Aysun Karabay; Duzova, Ali; Thurn, Daniela; Canpolat, Nur; Kaplan Bulut, Ipek; Azukaitis, Karolis; Obrycki, Lukasz; Ranchin, Bruno; Shroff, Rukshana; Candan, Cengiz; Erdogan, Hakan; et al. (Hypertension, 2025)
BACKGROUND: - Office blood pressure (BP) trajectories may help assess hypertension progression and the effects of antihypertensive treatment in children with chronic kidney disease. - METHODS: - Analysis of antihypertensive treatment and BP slopes in 320 patients from the 4C study (Cardiovascular Comorbidity in Children with Chronic Kidney Disease) cohort with chronic kidney disease before renal replacement therapy, based on a minimum of 3 individual observations and 2 years of follow-up. - RESULTS: - At enrollment, 70 (22%) patients had uncontrolled or untreated hypertension, 130 (41%) patients had controlled hypertension, and 120 (37%) patients had normotension without antihypertensive treatment. Antihypertensive treatment medication was prescribed for 53% of patients at baseline and initiated or added for 91 patients (AHT-I [group with intensification of antihypertensive treatment] group, 28%) during follow-up. Overall BP SD score remained stable over time in the cohort (β=−0.037±0.034, P=0.34 and −0.029±0.348, P=0.093 per year for systolic and diastolic BP SD score). In the AHT-I group, systolic and diastolic BP SD scores were higher at baseline and decreased significantly during follow-up (−0.22±0.07, P<0.003 and −0.12±0.05 SD score per year, P=0.01). Only 8 of 70 (11%) patients from the previously untreated/uncontrolled group remained untreated at the last observation, while 31 (44%) were controlled during follow-up. Of the 120 normotensive patients at baseline, 60% remained normotensive while 40% progressed to uncontrolled/untreated (n=23, 19%) or controlled (n=24, 20%) hypertension. - CONCLUSIONS: - Although the overall BP of the population remained stable over time, individual patterns of BP management showed considerable variability. BP control improved significantly with intensified antihypertensive therapy; however, a significant number of previously normotensive individuals developed new-onset hypertension during the observation period.